An Analysis Of Customer Satisfaction At Mie Gacoan Tengah Padang, Bengkulu City - Irem Saputra; Rika Dwi Yulihartika; Ana Nurmalia (Utami Publisher, 2026)
Mie Gacoan is one of the fast food businesses that is currently growing and gaining widespread attention in Bengkulu City. This study aims to analyze the factors that influence customer satisfaction at Mie Gacoan Tengah Padang in Bengkulu City, with the variables studied including product quality, service, restaurant environment, and price. The study used a quantitative method with data collection techniques through the distribution of questionnaires to 98 respondents and data analysis was performed using multiple linear regression with the help of the SPSS program. The results showed that simultaneously, all four variables had a significant effect on customer satisfaction, while partially, the variables of product quality, service, and price had a positive and significant effect, while the restaurant environment had a negative effect. Overall, the level of customer satisfaction was in the “satisfied” category with a percentage of 15.72%. These results indicate that customers are satisfied with the products and services provided, so Mie Gacoan needs to continue to improve product quality, service, and restaurant comfort to maintain customer satisfaction and loyalty.